Functional Outcomes of Frail Patients After Cardiac Surgery: An Observational Study. (June 2020) - Nakano, Mitsunori; Nomura, Yohei; Suffredini, Giancarlo; Bush, Brian; Tian, Jing; Yamaguchi, Atsushi; Walston, Jeremy; Hasan, Rani; Mandal, Kaushik; Schena, Stefano; Hogue, Charles W.; Brown, Charles H.
Abstract : BACKGROUND: Although frailty has been associated with major morbidity/mortality and increased length of stay after cardiac surgery, few studies have examined functional outcomes. We hypothesized that frailty would be independently associated with decreased functional status, increased discharge to a nonhome location, and longer duration of hospitalization after cardiac surgery, and that delirium would modify these associations. METHODS: This was an observational study nested in 2 trials, each of which was conducted by the same research team with identical measurement of exposures and outcomes. The Fried frailty scale was measured at baseline. The primary outcome (defined before data collection) was functional decline, defined as ≥2-point decline from baseline in Instrumental Activities of Daily Living (IADL) score at 1 month after surgery. Secondary outcomes were absolute decline in IADL score, discharge to a new nonhome location, and duration of hospitalization. Associations were analyzed using linear, logistic, and Poisson regression models with adjustments for variables considered before analysis (age, gender, race, and logistic European Score for Cardiac Operative Risk Evaluation [EuroSCORE]) and in a propensity score analysis. RESULTS: Data were available from 133 patients (83 from first trial and 50 from the second trial). The prevalence of frailty was 33% (44 of 133). In adjusted models, frail patients had increased odds of functional decline (primary outcome; odds ratio [OR], 2.41 [95% confidence interval CI, 1.03–5.63]; P = .04) and greater decline at 1 month in the secondary outcome of absolute IADL score (−1.48 [95% CI, −2.77 to −0.30]; P = .019), compared to nonfrail patients. Delirium significantly modified the association of frailty and change in absolute IADL score at 1 month. In adjusted hypothesis-generating models using secondary outcomes, frail patients had increased discharge to a new nonhome location (OR, 3.25 [95% CI, 1.37–7.69]; P = .007) and increased duration of hospitalization (1.35 days [95% CI, 1.19–1.52]; P < .0001) compared to nonfrail patients. The increased duration of hospitalization, but no change in functional status or discharge location, was partially mediated by increased complications in frail patients. CONCLUSIONS: Frailty may identify patients at risk of functional decline at 1 month after cardiac surgery. Perioperative strategies to optimize frail cardiac surgery patients are needed.